THE EFFECT OF DIFFERENTIATED LEARNING ON EFL ACHIEVEMENT: A META-ANALYSIS - Putri, Shalsa Aledya; Mujiono, Mujiono; Sulistyo, Teguh (Universitas Muhammadiyah Metro, 2025)
The present meta-analysis explored the effects of differentiated learning on EFL learners' achievements, examining the impact of various moderating factors․ The study synthesized eight experimental studies (2014–2025), adhering to PRISMA guidelines, and found that differentiated Instruction had a large, statistically significant effect on English achievement (Hedges' g = 1․92)․ Overall effect sizes were evaluated, and moderator analyses were applied to assess variation by educational level, language-learning target, and geographical region․ The study revealed that learners at the primary level demonstrated greater gains in English achievement than their secondary-level peers, suggesting age-related responsiveness to differentiated instruction․ The study showed that those who learned reading and writing skills improved more than those who learned general English language learning․ The findings indicate that differentiated learning can be aligned with learners' needs and characteristics to make the teaching–learning procedure more personalized and interactive․ This study, therefore, favors more research into finding how best differentiated learning can be implemented in different educational domains․